Rhenium-loaded nano flaky pure silicon S-1 zeolite catalyst as well as preparation method and application thereof

Through the rhenium-supported nanosheet-like pure silicon S-1 zeolite catalyst, the problem of insufficient research on the catalytic heterogeneous solid catalyst for the synthesis of medium-chain fatty acids and glycerides in the prior art was solved, and efficient and clean medium-chain glyceride synthesis was achieved, with good catalytic stability and environmental protection characteristics.

CN119793517APending Publication Date: 2025-04-11JIANGXI AGRICULTURAL UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510036452.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, there are few researches on high-efficiency heterogeneous solid catalysts that catalyze the synthesis of medium-chain fatty acids and glycerol esters, resulting in the limitation of the application of green and efficient catalysis.

Method used

A nanosheet-like pure silicon S-1 zeolite catalyst supported by a rhenium was prepared by hydrothermal synthesis method, and rhenium was introduced by an equal volume impregnation method to prepare a nanosheet-like pure silicon S-1 zeolite catalyst supported by rhenium.

Benefits of technology

The catalyst has excellent catalytic performance and good catalytic stability in the esterification reaction of caprylic acid and glycerol. The conversion rate of caprylic acid reaches 72.92%. The catalyst is not corrosive in equipment, is easy to separate and reuse, and has green and environmentally friendly characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793517A_ABST
    Figure CN119793517A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of synthesis of medium-chain glyceride, and particularly relates to a rhenium-loaded nano flaky pure silicon S-1 zeolite catalyst as well as a preparation method and application thereof. The preparation method comprises the following steps: by taking tetraethoxysilane as a silicon source, tetrapropylammonium hydroxide as a template agent and ammonia water and glucose as growth regulators, preparing by adopting a hydrothermal synthesis method, and drying and calcining to prepare a nano flaky pure silicon S-1 zeolite carrier; ammonium perrhenate is used as a rhenium source to prepare a rhenium precursor solution, the nanosheet-shaped pure silicon S-1 zeolite carrier is subjected to equivalent-volume impregnation, and the rhenium-loaded nanosheet-shaped pure silicon S-1 zeolite catalyst is obtained through aging, drying and calcination. The high-performance solid catalyst containing metal active sites on the surface is prepared, is applied to the esterification reaction of caprylic acid and glyceride to produce medium-chain glyceride, and has higher catalytic esterification activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of synthesis of medium-chain glycerides, and specifically relates to a rhenium-loaded nano-sheet pure silicon S-1 zeolite catalyst and a preparation method and application thereof. Background Art

[0002] Medium-chain glycerides are ester compounds formed by esterification reaction between glycerol and medium-chain fatty acids (mainly caprylic acid and capric acid), which mainly include medium-chain monoglycerides, medium-chain diglycerides and medium-chain triglycerides. Compared with long-chain triglycerides, medium-chain triglycerides have shorter carbon chains, are easy to digest and can quickly provide energy and other metabolic characteristics, and have important application prospects in the healthy edible oil market. In addition, medium-chain monoglycerides and medium-chain diglycerides have excellent emulsification, foaming, antibacterial, moisturizing and stabilizing properties, and are widely used in many industries such as food, medicine, cosmetics and chemicals. Because medium-chain glycerides naturally existing in nature are very rare, the synthesis of medium-chain glycerides by chemical catalysis of medium-chain fatty acids and glycerol esterification has important theoretical and practical significance.

[0003] The key to catalyzing the esterification of medium-chain fatty acids and glycerol to synthesize medium-chain glycerides lies in the preparation of high-performance catalysts. Currently, common catalysts are mainly acid catalysts and alkaline catalysts. Among them, liquid acid / base catalysts are homogeneous catalytic reaction systems in application, which have disadvantages such as difficulty in separating reaction products, difficulty in reusing liquid catalysts, and strong corrosion of acid / base solutions to equipment. However, there are few studies on efficient heterogeneous solid catalysts for catalyzing the esterification of medium-chain fatty acids and glycerol, resulting in limited application of green and efficient heterogeneous catalysis of medium-chain fatty acids and glycerol to synthesize medium-chain glycerides. Based on this, the development of novel, high-performance solid catalysts to achieve efficient and clean production of medium-chain glycerides has become an urgent problem that needs to be solved. Summary of the invention

[0004] The purpose of the present invention is to provide a rhenium-loaded nano-sheet pure silicon S-1 zeolite catalyst and a preparation method and application thereof. The prepared catalyst is a solid catalyst that can be used to catalyze the esterification of medium-chain fatty acids and glycerol to synthesize medium-chain fatty acid glycerides. It has no equipment corrosion, and the product is easy to separate, and the process is environmentally friendly.

[0005] The present invention solves the technical problem by adopting the following technical solutions: The object of the present invention is to provide a method for preparing a rhenium-loaded nano-sheet pure silicon S-1 zeolite catalyst, the preparation method comprising the following steps: Step 1: using tetraethyl orthosilicate as a silicon source, tetrapropylammonium hydroxide as a template, ammonia water and glucose as growth regulators, adopting a hydrothermal synthesis method to obtain a nano-sheet pure silicon S-1 zeolite carrier through drying and calcination; Step 2: prepare a rhenium precursor solution with ammonium perrhenate as a rhenium source, and impregnate it with the nano-sheet pure silicon S-1 zeolite carrier prepared in step 1 in equal volumes, and obtain a rhenium-loaded nano-sheet pure silicon S-1 zeolite catalyst after aging, drying and calcination; wherein the loading amount of rhenium element in the nano-sheet pure silicon S-1 zeolite carrier is 1% to 20%.

[0006] It should be noted that the rhenium element in the rhenium-loaded nanosheet pure silicon S-1 zeolite catalyst of the present invention is in an oxide state.

[0007] Furthermore, in step 2, the loading amount of rhenium element in the nano-sheet pure silicon S-1 zeolite carrier is 2% to 10%; Preferably, in step 2, the loading amount of rhenium element in the nano-sheet pure silicon S-1 zeolite carrier is 5% to 7%; Preferably, in step 2, the loading amount of rhenium element in the nano-sheet pure silicon S-1 zeolite carrier is 5%.

[0008] Furthermore, the calcination temperature in step 2 is 300° C. to 500° C., and the calcination time is 4 h to 6 h; Preferably, the calcination temperature in step 2 is 350° C. to 450° C., and the calcination time is 4.5 h to 5.5 h; Preferably, the calcination temperature in step 2 is 350° C. and the calcination time is 5 h.

[0009] Furthermore, in step 2, the drying temperature is 100° C. to 140° C., and the drying time is 6 h to 24 h; Preferably, in step 2, the drying temperature is 120° C. and the drying time is 12 h.

[0010] Furthermore, in step 2, the aging is an aging treatment in air for 12 hours to 48 hours.

[0011] Further, in step 1, the raw materials for preparing the nano-sheet pure silicon S-1 zeolite carrier are, in terms of effective ingredients, the molar ratio of SiO2, TPAOH, NH3, Glu, and H2O is 1: (0.20-0.28): (0.5-0.7): (0.20-0.28): 10.0; Preferably, in step 1, the raw materials for preparing the nano-sheet pure silicon S-1 zeolite carrier are prepared in a molar ratio of SiO2, TPAOH, NH3, Glu and H2O of 1:0.24:0.62:0.24:10.0 based on the effective ingredients.

[0012] Furthermore, in step 1, the hydrothermal crystallization temperature of the hydrothermal synthesis method is 95°C to 115°C, and the hydrothermal crystallization time is 72h to 120h; the drying temperature is 100°C to 140°C, and the drying time is 12h to 48h; the calcination temperature is 500°C to 600°C, and the calcination time is 4h to 6h; Preferably, in step one, the hydrothermal crystallization temperature of the hydrothermal synthesis method is 105°C, and the hydrothermal crystallization time is 96 hours; the drying temperature is 120°C, and the drying time is 24 hours; the calcination temperature is 550°C, and the calcination time is 5 hours.

[0013] Furthermore, the preparation method of the above-mentioned rhenium-loaded nano-sheet pure silicon S-1 zeolite catalyst comprises the following steps: Step 1: Using tetraethyl orthosilicate as a silicon source, tetrapropylammonium hydroxide as a template, and ammonia and glucose as growth regulators, tetraethyl orthosilicate is added dropwise to an aqueous solution of tetrapropylammonium hydroxide, and after the addition is completed, ammonia and glucose are added thereto, the resulting mixed solution is stirred and aged at room temperature, and then hydrothermally crystallized, and the crystallized product is then washed, dried, ground, and calcined to obtain a nano-sheet pure silicon S-1 zeolite carrier; Step 2: Prepare a rhenium precursor solution with ammonium perrhenate as the rhenium source, and use the equal volume impregnation method to drop the rhenium precursor solution on the nanosheet pure silicon S-1 zeolite carrier described in step 1. After impregnation and aging treatment, it is dried, ground and calcined to obtain a rhenium-loaded nanosheet pure silicon S-1 (Re / S-1-p) zeolite catalyst.

[0014] The "equal volume impregnation method" in the present invention refers to a method for preparing a supported catalyst by impregnation using an impregnation liquid volume that is equal to the pore volume of the solid support.

[0015] Another object of the present invention is to provide a rhenium-loaded nano-sheet pure silicon S-1 zeolite catalyst obtained by the above preparation method; Preferably, the rhenium-loaded nano-sheet pure silicon S-1 zeolite catalyst is a sheet-like MFI topological framework structure; Preferably, the thickness of the rhenium-loaded nanosheet pure silicon S-1 zeolite catalyst is 180 nm to 220 nm.

[0016] Another object of the present invention is to provide the use of the above-mentioned rhenium-loaded nano-sheet pure silicon S-1 zeolite catalyst in catalyzing the esterification reaction of caprylic acid and glycerol to synthesize medium-chain glycerides; Preferably, the method for catalyzing the esterification reaction of caprylic acid and glycerol to synthesize medium-chain glycerides is as follows: using caprylic acid and glycerol as raw materials, adding a rhenium-loaded nano-sheet pure silicon S-1 zeolite catalyst, placing in a high-pressure sealed container, stirring and reacting at 90° C. to 110° C. for 7 h to 9 h, centrifuging and layering (the upper layer is medium-chain glycerides) after the reaction is completed to obtain medium-chain glycerides; Preferably, the medium-chain glycerides include, by weight percentage, 73% to 87% of medium-chain monoglycerides, 10% to 25% of medium-chain diglycerides and 0.3% to 3.0% of medium-chain triglycerides.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The nano-sheet pure silicon S-1 zeolite catalyst loaded with rhenium provided by the present invention uses tetraethyl orthosilicate as a silicon source, tetrapropylammonium hydroxide as a template agent, ammonia water and glucose as growth regulators, a nano-sheet pure silicon S-1 zeolite prepared by a hydrothermal synthesis method as a carrier, and ammonium perrhenate as a rhenium source to prepare a rhenium precursor solution, and rhenium is introduced into the catalyst by an impregnation method to obtain the nano-sheet pure silicon S-1 zeolite catalyst loaded with rhenium. Experiments have confirmed that the nano-sheet pure silicon S-1 zeolite catalyst loaded with rhenium prepared by the present invention can be used for the catalytic esterification of octanoic acid and glycerol to prepare medium-chain fatty acid glycerides.

[0018] 2. The rhenium-loaded nano-sheet pure silicon S-1 zeolite catalyst prepared by the present invention has rhenium highly dispersed on the surface of the nano-sheet pure silicon S-1 zeolite, and rhenium and the nano-sheet pure silicon S-1 zeolite have good adsorption and binding effects, and Re can be evenly and densely distributed on the catalyst surface. The interaction of this structural advantage and chemical properties enables the 5Re / S-1-p (350℃) solid catalyst to exhibit excellent catalytic performance and good catalytic stability in the esterification reaction of octanoic acid and glycerol, and the octanoic acid conversion can reach 72.92%.

[0019] 3. The catalyst prepared by the present invention is used for the synthesis of medium-chain fatty acid glycerides from caprylic acid and glycerol esterification without obvious equipment corrosion, and the catalyst is highly safe to use. The catalyst is insoluble in the reaction raw materials and products, is easy to separate, and can be reused after simple treatment. The reaction products can be separated by layering without complex post-treatment processes. The process produces almost no wastewater and has green and environmentally friendly characteristics. The catalyst provided in this application also has the advantage of a simple and easy preparation process. The catalyst prepared by the present invention has a good prospect for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 These are scanning electron microscope images and transmission electron microscope images (a, b) of the nano-sheet pure silicon S-1 zeolite catalyst prepared in comparative example 1 of the present invention and scanning electron microscope images and transmission electron microscope images (c, d) of the 5Re / S-1-p (350°C) catalyst prepared in the embodiment.

[0021] Figure 2 It is the X-ray diffraction pattern of the nano-sheet pure silicon S-1 zeolite catalyst prepared in Comparative Example 1 of the present invention and the 5Re / S-1-p (350°C) catalyst prepared in Example.

[0022] Figure 3 It is a N2 physical adsorption and desorption diagram of the nano-sheet pure silicon S-1 zeolite catalyst prepared in Comparative Example 1 of the present invention and the 5Re / S-1-p (350°C) catalyst prepared in Example. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0025] Reagents and raw materials: tetrapropylammonium hydroxide (TPAOH, 25% aqueous solution by mass, Kent Catalyst Technology Co., Ltd.), tetraethyl orthosilicate (TEOS, Tianjin Komiou Chemical Reagent Co., Ltd.), ammonia water (NH3·H2O, 25% aqueous solution by mass, Xilong Chemical Co., Ltd.), glucose (Glu, Shanghai McLean Biochemical Technology Co., Ltd.), ammonium perrhenate (NH4ReO4, Shanghai Aladdin Biochemical Technology Co., Ltd.), caprylic acid (CA, Shanghai McLean Biochemical Technology Co., Ltd.), glycerol (Gly, Xilong Chemical Co., Ltd.).

[0026] Examples 1 to 5: Preparation of Nano-Flake Pure Silicon S-1 Zeolite Supported Rhenium (5Re / S-1-p) Solid Catalyst at Different Calcination Temperatures 1. Preparation of Nano-Flake Pure Silica Zeolite (S-1-p) According to the molar ratio of SiO2:TPAOH:NH3:Glu:H2O of 1:0.24:0.62:0.24:10, 59.6g of 25% tetrapropylammonium hydroxide and 30g of distilled water were accurately weighed and added to a three-necked flask, and aged and stirred for 10 minutes. Then, 63g of tetraethyl orthosilicate was slowly added dropwise to the three-necked flask under vigorous stirring. After the addition was completed, 12.77g of ammonia water and 12.97g of glucose were weighed and added to the above mixed system. The mixed solution was vigorously stirred and aged at room temperature for 2h, and then transferred to a stainless steel crystallization kettle for hydrothermal crystallization at 105℃ for 96h; after the crystallization was completed, the mixture was washed with distilled water until it was neutral and dried in an oven at 120℃ for 12h; finally, the dried solid was ground into powder, placed in a muffle furnace and calcined at 550℃ for 5h in an air atmosphere to obtain nano-flaky pure silicon zeolite (S-1-p).

[0027] 2. Preparation of Nano-sheet Pure Silicon S-1 Zeolite Supported Rhenium (5Re / S-1-p) Solid Catalyst at Different Calcination Temperatures A certain amount of NH4ReO4 (equivalent to 5wt% of the theoretical rhenium loading in the carrier) was dissolved in distilled water to obtain an aqueous solution of NH4ReO4 of a certain concentration, which was slowly added drop by drop on the above-mentioned S-1-p zeolite by an equal volume impregnation method and aged in air for 24 hours; then it was placed in an oven at 120°C and dried for 12 hours; finally, the dried solid catalyst was ground into powder and placed in a muffle furnace in an air atmosphere, and calcined at T°C (T=300, 350, 400, 450, 500) for 5 hours to obtain a nanosheet-like pure silicon S-1 zeolite-loaded rhenium solid catalyst, marked as 5Re / S-1-p (T°C) (T=300, 350, 400, 450, 500).

[0028] Examples 6 to 9: Nano-sheet pure silicon S-1 zeolite loaded with rhenium ( x Preparation of Re / S-1-p (350℃) solid catalyst 1. Preparation of pure silica zeolite (S-1-p) with nanosheet structure 59.6 g of 25% tetrapropylammonium hydroxide and 30 g of distilled water were accurately weighed according to the molar ratio of SiO2:TPAOH:NH3:Glu:H2O of 1:0.24:0.62:0.24:10, added to a three-necked flask, aged with stirring for 10 min, then 63 g of tetraethyl orthosilicate was slowly added dropwise to the three-necked flask under vigorous stirring, after the addition was completed, 12.77 g of ammonia water and 12.97 g of glucose were weighed and added to the above mixed system, the mixed solution was vigorously stirred and aged at room temperature for 2 h, and then transferred to a stainless steel crystallization kettle for hydrothermal crystallization at 105°C for 96 h; after the crystallization was completed, the mixture was washed with distilled water until neutral and dried at 120°C overnight; finally, the dried solid was ground into powder, placed in a muffle furnace and calcined at 550°C for 5 h in an air atmosphere to obtain pure silicon zeolite (S-1-p) with a nano-sheet structure.

[0029] 2. Preparation of Nano-sheet Pure Silicon S-1 Zeolite Supported Rhenium (Re / S-1-p) Solid Catalyst A certain amount of NH4ReO4 (equivalent to xwt% of the theoretical rhenium loading in the carrier) was dissolved in distilled water to obtain NH4ReO4 aqueous solutions of different concentrations, which were slowly added drop by drop on the above-mentioned S-1-p zeolite by an equal volume impregnation method and aged in air for 24 h; then, it was placed in an oven at 120°C for 12 h; finally, the dried solid catalyst was ground into powder and placed in a muffle furnace and calcined at 350°C for 5 h in an air atmosphere to obtain a nano-sheet pure silicon S-1 zeolite loaded with rhenium solid catalyst, marked as x Re / S-1-p(350℃)( x =1, 2, 7, 10).

[0030] Comparative Example 1: Preparation of Nano-Flake Pure Silica Zeolite (S-1-p) 59.6 g of 25% tetrapropylammonium hydroxide and 30 g of distilled water were accurately weighed according to the molar ratio of SiO2:TPAOH:NH3:Glu:H2O of 1:0.24:0.62:0.24:10, added to a three-necked flask, aged with stirring for 10 min, then 63 g of tetraethyl orthosilicate was slowly added dropwise to the three-necked flask under vigorous stirring, after the addition was completed, 12.77 g of ammonia water and 12.97 g of glucose were weighed and added to the above mixed system, the mixed solution was vigorously stirred and aged at room temperature for 2 h, and then transferred to a stainless steel crystallization kettle for hydrothermal crystallization at 105°C for 96 h; after the crystallization was completed, the mixture was washed with distilled water until it was neutral and dried in an oven at 120°C overnight; finally, the dried solid was ground into powder, placed in a muffle furnace and calcined at 550°C for 5 h in an air atmosphere to obtain pure silicon zeolite (S-1-p) with a nano-sheet structure.

[0031] Comparative Example 2: Preparation of a flake silica-alumina zeolite ZSM-5 loaded with rhenium (5Re / ZSM-5-p) solid catalyst 1. Preparation of flake-structured silica-alumina zeolite (ZSM-5-p) According to the molar ratio of SiO2:Al2O3:TPAOH:urea:H2O:NaOH:IPA=1:0.0074:0.3:0.6:29:0.05:0.03, 39.3g 25% tetrapropylammonium hydroxide and 55.2g distilled water were accurately weighed and stirred for 10 minutes. Then, 33.6g ethyl orthosilicate was slowly added dropwise to the tetrapropylammonium hydroxide solution system under vigorous stirring. After the addition was completed, 0.3g isopropanol and 0.3g sodium hydroxide were weighed and added to the above system. , after stirring for 10 minutes, 0.9g of aluminum nitrate nonahydrate was added to the system, and after continuing to stir for 10 minutes, 6.0g of urea was added to the solution system. The mixture was vigorously stirred and aged at room temperature for 6 hours, and then transferred to a stainless steel crystallization kettle for hydrothermal crystallization at 180°C for 48 hours; after the crystallization was completed, the obtained product was washed with distilled water until neutral, and dried in an oven at 100°C overnight; the dried solid was ground into powder, placed in a muffle furnace and calcined at 550°C for 5 hours in an air atmosphere to obtain flaky ZSM-5-p zeolite.

[0032] 2. Preparation of sheet-like silica-alumina zeolite supported rhenium (5Re / ZSM-5-p) solid catalyst A certain amount of NH4ReO4 (equivalent to 5wt% of the theoretical rhenium loading in the carrier) was dissolved in distilled water to obtain an aqueous solution of NH4ReO4 of a certain concentration, which was slowly added dropwise onto the above-mentioned ZSM-5-p zeolite by an equal volume impregnation method and aged in air for 24 hours; then it was placed in an oven at 120°C and dried for 12 hours; finally, the dried solid catalyst was ground into powder and placed in a muffle furnace and calcined at 350°C for 5 hours in an air atmosphere to obtain a flaky silica-alumina zeolite-loaded rhenium solid catalyst, marked as 5Re / ZSM-5-p (350°C).

[0033] Test example The nano-sheet pure silicon S-1 zeolite supported rhenium solid catalyst prepared in the example is characterized and its performance is tested as follows.

[0034] 1. Characterization and analysis of nanosheet pure silicon S-1 zeolite supported rhenium solid catalyst (1) Pure silica zeolite (5Re / S-1-p) synthesized by calcining at 350°C with a 5wt% Re loading was used as the test sample, and nano-sheet pure silica zeolite (S-1-p) was used as the control. During the analysis, a scanning electron microscope (SUPRA55, Carl Zeiss, Germany) was used for characterization under high vacuum conditions and an accelerating voltage of 5kV to facilitate observation and analysis of the microstructure of the sample. The image of the scanning electron microscope is shown in Figure 2. Figure 1 As shown (a, c); (2) Using 5 wt% Re loading and calcined at 350 °C, the synthesized nanosheet-shaped pure silica zeolite (5Re / S-1-p) was used as the test sample, and nanosheet-shaped pure silica zeolite (S-1-p) was used as the control. The samples were characterized and analyzed using a transmission electron microscope (JEM-2100, JEOL Ltd.) at an accelerating voltage of 200 kV, a point resolution of 0.23 nm, and a line resolution of 0.14 nm. The following results were obtained: Figure 1 (b, d) Transmission electron microscopy images shown; pass Figure 1 (a, b) It can be observed that the nanosheet-like pure silicon S-1 zeolite supported rhenium solid catalyst is elliptical in shape, and the pure silicon zeolite S-1-p and nanosheet-like pure silicon S-1 zeolite supported rhenium 5Re / S-1-p catalysts have similar smooth surfaces and morphologies, with a b-axis thickness of about 200 nm. Figure 1 The transmission electron microscopy images in (c, d) further illustrate the above phenomenon, indicating that the introduction of metal Re does not destroy the size and morphology of nanosheet-like pure silicon S-1 zeolite.

[0035] In addition, it should be noted that the morphology and structure of the nano-sheet pure silicon S-1 zeolite loaded with rhenium solid catalyst 5Re / S-1-p synthesized at different calcination temperatures (300°C, 400°C, 450°C, 500°C), different loading amounts of Re (1%, 2%, 7%, 10%) and the nano-sheet pure silicon zeolite solid catalyst 5Re / S-1-p with 5wt% Re loading (350°C) are basically consistent.

[0036] 2. Crystalline structure of nanosheet pure silicon S-1 zeolite supported rhenium solid catalyst Nano-flaky pure silica zeolite (5Re / S-1-p) synthesized by calcination at 350°C with 5 wt% Re loading was used as the test sample, and nano-flaky pure silica zeolite (S-1-p) was used as the control. The microscopic crystal structure of all catalysts was studied by X-ray diffraction (XRD). The instrument model was RIGAKU Ultima IV diffractometer (Rigaku, Japan), the scanning step was 0.02°, CuKα was used as the source, the scanning range was 5-70°, and the scanning rate was 10°min -1 . Get Figure 2 X-ray diffraction pattern shown.

[0037] from Figure 2 It can be clearly observed in the X-ray diffraction pattern that both samples have 5 diffraction peaks at 7.9°, 8.8°, 23.0°, 23.8° and 24.5°, indicating the existence of MFI topological structure. This also shows that the MFI framework and crystal structure of S-1-p are not destroyed after the introduction of Re species. In addition, no Re species were found in the X-ray diffraction pattern, which shows that the metal Re has been highly dispersed on the surface of S-1-p, indicating that the nanosheet-like pure silicon S-1 zeolite loaded with rhenium synthesized in this experiment is a solid catalyst with good metal dispersion.

[0038] In addition, it should be noted that the microscopic crystal structures of the nano-sheet pure silicon S-1 zeolite loaded with rhenium solid catalyst 5Re / S-1-p synthesized at different calcination temperatures (300°C, 400°C, 450°C, 500°C), different loading amounts of Re (1%, 2%, 7%, 10%) and the nano-sheet pure silicon zeolite solid catalyst with 5wt% Re loading (5Re / S-1-p(350°C)) are basically consistent.

[0039] 3. Surface structure of nanosheet pure silicon S-1 zeolite supported rhenium solid catalyst Nano-flaky pure silica zeolite (5Re / S-1-p) synthesized by calcining at 350°C with 5wt% Re loading was used as the test sample, and nano-flaky pure silica zeolite (S-1-p) was used as the control. The specific surface area and pore structure of the sample catalyst were characterized by N2 physical adsorption and desorption using a Micromeritics ASAP2020M instrument (Micromeritics Instruments, USA). The sample was pretreated in liquid nitrogen at -196°C and degassed at 200°C for 10 hours. The specific surface area and pore size distribution of the sample were calculated according to the Brunauer-Emmett-Teller (BET) equation and the Barrett-Joyner-Halenda (BJH) model.

[0040] Depend on Figure 3 It can be seen that the catalyst samples have similar pore structures and hysteresis loops, all of which are I-type isotherms. With the introduction of Re, the hysteresis loop changes, which may be due to the introduction of Re occupying part of the intercrystalline stacking mesopores of the carrier S-1-p, indicating that the introduction of Re has an effect on the pore structure of pure silica zeolite S-1-p.

[0041] In addition, it should be noted that the pore structures of the nanosheet pure silicon S-1 zeolite loaded with rhenium solid catalyst 5Re / S-1-p synthesized at different calcination temperatures (300℃, 400℃, 450℃, 500℃) and the nanosheet pure silicon zeolite solid catalyst with 5wt% Re loading (5Re / S-1-p(350℃)) are slightly different. With the increase of calcination temperature, the specific surface area and surface area of ​​the catalyst gradually increase, the mesopore volume also increases slightly, while the micropore volume remains basically unchanged, indicating that Re will present different states at different calcination temperatures. Since the rhenium precursor will sublime at high temperature, its influence on the pore structure is also different.

[0042] 4. Preparation of medium-chain glycerides by esterification of caprylic acid and glycerol catalyzed by nano-sheet pure silicon S-1 zeolite supported by rhenium solid catalyst: (1) The esterification of caprylic acid and glycerol to prepare medium-chain glycerides was catalyzed by a 5% Re-loaded nano-sheet pure silica zeolite solid catalyst (5Re / S-1-p (300°C)) calcined at 300°C: In this experiment, 6.26 g of caprylic acid and 4.00 g of glycerol were weighed according to the molar ratio of caprylic acid to glycerol of 1:1, and then 0.1 g of 5Re / S-1-p (300℃) catalyst was weighed. They were added to a 25 ml hydrothermal reactor, sealed and placed in a 100℃ oil bath for stirring and reaction for 8 hours, and then centrifuged. The centrifugal speed was set to 10000 rpm for 8 minutes to obtain three phases: mixed product phase, glycerol phase and solid catalyst phase. The obtained mixed product phase was analyzed by Agilent-7890B gas chromatograph (Agilent Technologies, USA) flame ionization detector (FID) and HP-5 capillary column (30m×0.32mm×0.50μm), and the caprylic acid (CA) conversion rate and the selectivity of medium-chain monoglyceride (MCM), medium-chain diglyceride (MCD) and medium-chain triglyceride (MCT) were calculated according to the following formulas. After analysis and calculation, it was concluded that the conversion rate of caprylic acid was 32.73%, while the selectivity of medium-chain monoglycerides, medium-chain diglycerides and medium-chain triglycerides reached 82.15%, 16.88% and 0.97%, respectively.

[0043] The calculation formulas for caprylic acid conversion and medium-chain glyceride selectivity are as follows:

[0044] In the formula, X CA represents the conversion rate of octanoic acid (%); S MCM , S MCD , S MCTrepresents the selectivity (%) of medium-chain glycerol monoesters, diglycerides, and triesters, respectively; and n CA Indicates the molar content of octanoic acid before the reaction and the molar content of octanoic acid remaining after the reaction (mol), n MCM 、n MCD and n MCT Represent the molar content (mol) of medium-chain monoglycerides, medium-chain diglycerides and medium-chain triglycerides, respectively.

[0045] (2) The esterification of caprylic acid and glycerol to prepare medium-chain glycerides was catalyzed by a 5% Re-loaded nano-sheet pure silica zeolite solid catalyst (5Re / S-1-p (350°C)) calcined at 350°C: In this experiment, 6.26 g of caprylic acid and 4.00 g of glycerol were weighed according to the molar ratio of caprylic acid to glycerol of 1:1, and then 0.1 g of 5Re / S-1-p (350℃) catalyst was weighed. They were added to a 25 ml hydrothermal reactor, sealed and placed in a 100℃ oil bath for stirring and reaction for 8 hours, and then centrifuged. The centrifugal speed was set to 10000 rpm for 8 minutes to obtain three phases: mixed product phase, glycerol phase and solid catalyst phase. The obtained mixed product phase was analyzed by Agilent-7890B gas chromatograph (Agilent Technologies, USA) flame ionization detector (FID) and HP-5 capillary column (30m×0.32mm×0.50μm), and the caprylic acid (CA) conversion rate and the selectivity of medium-chain monoglyceride (MCM), medium-chain diglyceride (MCD) and medium-chain triglyceride (MCT) were calculated according to the following formulas. After analysis and calculation, it was concluded that the conversion rate of caprylic acid was 68.16%, while the selectivity of medium-chain monoglycerides, medium-chain diglycerides and medium-chain triglycerides reached 80.71%, 18.56% and 0.73%, respectively.

[0046] The calculation methods of caprylic acid conversion rate and medium-chain glyceride selectivity are the same as above.

[0047] (3) The esterification of caprylic acid and glycerol to prepare medium-chain glycerides was catalyzed by a 5% Re-loaded nano-sheet pure silica zeolite solid catalyst (5Re / S-1-p (400°C)) calcined at 400°C: In this experiment, 6.26 g of caprylic acid and 4.00 g of glycerol were weighed according to the molar ratio of caprylic acid to glycerol of 1:1, and then 0.1 g of 5Re / S-1-p (400℃) catalyst was weighed. They were added to a 25 ml hydrothermal reactor, sealed and placed in a 100℃ oil bath for stirring and reaction for 8 hours, and then centrifuged. The centrifugal speed was set to 10000 rpm for 8 minutes to obtain three phases: mixed product phase, glycerol phase and solid catalyst phase. The obtained mixed product phase was analyzed by Agilent-7890B gas chromatograph (Agilent Technologies, USA) flame ionization detector (FID) and HP-5 capillary column (30m×0.32mm×0.50μm), and the caprylic acid (CA) conversion rate and the selectivity of medium-chain monoglyceride (MCM), medium-chain diglyceride (MCD) and medium-chain triglyceride (MCT) were calculated according to the following formulas. After analysis and calculation, it was concluded that the conversion rate of caprylic acid was 52.23%, while the selectivity of medium-chain monoglycerides, medium-chain diglycerides and medium-chain triglycerides reached 73.89%, 23.34% and 2.78%, respectively.

[0048] The calculation methods of caprylic acid conversion rate and medium-chain glyceride selectivity are the same as above.

[0049] (4) The esterification of caprylic acid and glycerol to prepare medium-chain glycerides was catalyzed by a 5% Re-loaded nano-sheet pure silica zeolite solid catalyst (5Re / S-1-p (450°C)) calcined at 450°C: In this experiment, 6.26 g of caprylic acid and 4.00 g of glycerol were weighed according to the molar ratio of caprylic acid to glycerol of 1:1, and then 0.1 g of 5Re / S-1-p (450℃) catalyst was weighed. They were added to a 25 ml hydrothermal reactor, sealed and placed in a 100℃ oil bath for stirring and reaction for 8 hours, and then centrifuged. The centrifugal speed was set to 10000 rpm for 8 minutes to obtain three phases: mixed product phase, glycerol phase and solid catalyst phase. The obtained mixed product phase was analyzed by Agilent-7890B gas chromatograph (Agilent Technologies, USA) flame ionization detector (FID) and HP-5 capillary column (30m×0.32mm×0.50μm), and the caprylic acid (CA) conversion rate and the selectivity of medium-chain monoglyceride (MCM), medium-chain diglyceride (MCD) and medium-chain triglyceride (MCT) were calculated according to the following formulas. After analysis and calculation, it was concluded that the conversion rate of caprylic acid was 49.54%, while the selectivity of medium-chain monoglycerides, medium-chain diglycerides and medium-chain triglycerides reached 73.95%, 23.60% and 2.45%, respectively.

[0050] The calculation methods of caprylic acid conversion rate and medium-chain glyceride selectivity are the same as above.

[0051] (5) The esterification of caprylic acid and glycerol to prepare medium-chain glycerides was catalyzed by a 5% Re-loaded nano-sheet pure silica zeolite solid catalyst (5Re / S-1-p (500°C)) calcined at 500°C: In this experiment, 6.26 g of caprylic acid and 4.00 g of glycerol were weighed according to the molar ratio of caprylic acid to glycerol of 1:1, and then 0.1 g of 5Re / S-1-p (500℃) catalyst was weighed. They were added to a 25 ml hydrothermal reactor, sealed and placed in a 100℃ oil bath for stirring and reaction for 8 hours, and then centrifuged. The centrifugal speed was set to 10000 rpm for 8 minutes to obtain three phases: mixed product phase, glycerol phase and solid catalyst phase. The obtained mixed product phase was analyzed by Agilent-7890B gas chromatograph (Agilent Technologies, USA) flame ionization detector (FID) and HP-5 capillary column (30m×0.32mm×0.50μm), and the caprylic acid (CA) conversion rate and the selectivity of medium-chain monoglyceride (MCM), medium-chain diglyceride (MCD) and medium-chain triglyceride (MCT) were calculated according to the following formulas. After analysis and calculation, it was concluded that the conversion rate of caprylic acid was 32.40%, while the selectivity of medium-chain monoglycerides, medium-chain diglycerides and medium-chain triglycerides reached 86.86%, 12.36% and 0.78%, respectively.

[0052] The calculation methods of caprylic acid conversion rate and medium-chain glyceride selectivity are the same as above.

[0053] (6) The esterification of caprylic acid and glycerol to prepare medium-chain glycerides was catalyzed by a 1% Re-loaded nano-sheet pure silica zeolite solid catalyst (1Re / S-1-p (350°C)) calcined at 350°C: In this experiment, 6.26 g of caprylic acid and 4.00 g of glycerol were weighed according to the molar ratio of caprylic acid to glycerol of 1:1, and then 0.1 g of 1Re / S-1-p (350℃) catalyst was weighed. They were added to a 25 ml hydrothermal reactor, sealed and placed in a 100℃ oil bath for stirring and reaction for 8 hours, and then centrifuged. The centrifugal speed was set to 10000 rpm for 8 minutes to obtain three phases: mixed product phase, glycerol phase and solid catalyst phase. The obtained mixed product phase was analyzed by Agilent-7890B gas chromatograph (Agilent Technologies, USA) flame ionization detector (FID) and HP-5 capillary column (30m×0.32mm×0.50μm), and the caprylic acid (CA) conversion rate and the selectivity of medium-chain monoglyceride (MCM), medium-chain diglyceride (MCD) and medium-chain triglyceride (MCT) were calculated according to the following formulas. After analysis and calculation, it was concluded that the conversion rate of caprylic acid was 54.79%, while the selectivity of medium-chain monoglycerides, medium-chain diglycerides and medium-chain triglycerides reached 86.04%, 13.55% and 0.41%, respectively.

[0054] The calculation methods of caprylic acid conversion rate and medium-chain glyceride selectivity are the same as above.

[0055] (7) The esterification of caprylic acid and glycerol to prepare medium-chain glycerides was catalyzed by a 2% Re-loaded nano-sheet pure silica zeolite solid catalyst (2Re / S-1-p (350°C)) calcined at 350°C: In this experiment, 6.26 g of caprylic acid and 4.00 g of glycerol were weighed according to the molar ratio of caprylic acid to glycerol of 1:1, and then 0.1 g of 2Re / S-1-p (350℃) catalyst was weighed. They were added to a 25 ml hydrothermal reactor, sealed and placed in a 100℃ oil bath for stirring and reaction for 8 hours, and then centrifuged. The centrifugal speed was set to 10000 rpm for 8 minutes to obtain three phases: mixed product phase, glycerol phase and solid catalyst phase. The obtained mixed product phase was analyzed by Agilent-7890B gas chromatograph (Agilent Technologies, USA) flame ionization detector (FID) and HP-5 capillary column (30m×0.32mm×0.50μm), and the caprylic acid (CA) conversion rate and the selectivity of medium-chain monoglyceride (MCM), medium-chain diglyceride (MCD) and medium-chain triglyceride (MCT) were calculated according to the following formulas. After analysis and calculation, it was concluded that the conversion rate of caprylic acid was 61.68%, while the selectivity of medium-chain monoglycerides, medium-chain diglycerides and medium-chain triglycerides reached 83.86%, 15.65% and 0.49%, respectively.

[0056] The calculation methods of caprylic acid conversion rate and medium-chain glyceride selectivity are the same as above.

[0057] (8) The 7% Re loading nano-sheet pure silica zeolite solid catalyst (7Re / S-1-p (350°C)) calcined at 350°C catalyzes the esterification of caprylic acid with glycerol to prepare medium-chain glycerides: In this experiment, 6.26 g of caprylic acid and 4.00 g of glycerol were weighed according to the molar ratio of caprylic acid to glycerol of 1:1, and then 0.1 g of 7Re / S-1-p (350℃) catalyst was weighed. They were added to a 25 ml hydrothermal reactor, sealed and placed in a 100℃ oil bath for stirring and reaction for 8 hours, and then centrifuged. The centrifugal speed was set to 10000 rpm for 8 minutes to obtain three phases: mixed product phase, glycerol phase and solid catalyst phase. The obtained mixed product phase was analyzed by Agilent-7890B gas chromatograph (Agilent Technologies, USA) flame ionization detector (FID) and HP-5 capillary column (30m×0.32mm×0.50μm), and the caprylic acid (CA) conversion rate and the selectivity of medium-chain monoglyceride (MCM), medium-chain diglyceride (MCD) and medium-chain triglyceride (MCT) were calculated according to the following formulas. After analysis and calculation, it was concluded that the conversion rate of caprylic acid was 68.47%, while the selectivity of medium-chain monoglycerides, medium-chain diglycerides and medium-chain triglycerides reached 80.22%, 18.45% and 1.33%, respectively.

[0058] The calculation methods of caprylic acid conversion rate and medium-chain glyceride selectivity are the same as above.

[0059] (9) The esterification of caprylic acid and glycerol to prepare medium-chain glycerides was catalyzed by a 10% Re-loaded nano-sheet pure silica zeolite solid catalyst (10Re / S-1-p (350℃)) calcined at 350℃: In this experiment, 6.26 g of caprylic acid and 4.00 g of glycerol were weighed according to the molar ratio of caprylic acid to glycerol of 1:1, and then 0.1 g of 10Re / S-1-p (350℃) catalyst was weighed. They were added to a 25 ml hydrothermal reactor, sealed and placed in a 100℃ oil bath for stirring and reaction for 8 hours, and then centrifuged. The centrifugal speed was set to 10000 rpm for 8 minutes to obtain three phases: mixed product phase, glycerol phase and solid catalyst phase. The obtained mixed product phase was analyzed by Agilent-7890B gas chromatograph (Agilent Technologies, USA) flame ionization detector (FID) and HP-5 capillary column (30m×0.32mm×0.50μm), and the caprylic acid (CA) conversion rate and the selectivity of medium-chain monoglyceride (MCM), medium-chain diglyceride (MCD) and medium-chain triglyceride (MCT) were calculated according to the following formulas. After analysis and calculation, it was concluded that the conversion rate of caprylic acid was 72.92%, while the selectivity of medium-chain monoglycerides, medium-chain diglycerides and medium-chain triglycerides reached 76.92%, 20.52% and 2.56%, respectively.

[0060] The calculation methods of caprylic acid conversion rate and medium-chain glyceride selectivity are the same as above.

[0061] (10) Nano-flaky pure silica zeolite (S-1-p) (Comparative Example 1) catalyzes the esterification of caprylic acid and glycerol to prepare medium-chain glycerides: In this experiment, 6.26 g of caprylic acid and 4.00 g of glycerol were weighed according to the molar ratio of caprylic acid to glycerol of 1:1, and then 0.1 g of S-1-p (350 ° C) catalyst was weighed. They were added to a 25 ml hydrothermal reactor, sealed and placed in a 100 ° C oil bath for stirring and reaction for 8 hours, and then centrifuged. The centrifugal speed was set to 10000 rpm for 8 minutes to obtain three phases: mixed product phase, glycerol phase and solid catalyst phase. The obtained mixed product phase was analyzed by Agilent-7890B gas chromatograph (Agilent Technologies, USA) flame ionization detector (FID) and HP-5 capillary column (30m×0.32mm×0.50μm), and the caprylic acid (CA) conversion rate and the selectivity of medium-chain monoglyceride (MCM), medium-chain diglyceride (MCD) and medium-chain triglyceride (MCT) were calculated according to the following formulas. After analysis and calculation, it was concluded that the conversion rate of caprylic acid was 38.40%, while the selectivity of medium-chain monoglycerides, medium-chain diglycerides and medium-chain triglycerides reached 83.13%, 16.06% and 0.80%, respectively.

[0062] The calculation methods of caprylic acid conversion rate and medium-chain glyceride selectivity are the same as above.

[0063] (11) Flaky silica-alumina zeolite supported Re (5Re / ZSM-5-p) solid catalyst (Comparative Example 2) catalyzes the esterification of caprylic acid and glycerol to prepare medium-chain glycerides: In this experiment, 6.26 g of caprylic acid and 4.00 g of glycerol were weighed according to the molar ratio of caprylic acid to glycerol of 1:1, and then 0.1 g of 5Re / ZSM-5-p (350℃) catalyst was weighed. They were added to a 25 ml hydrothermal reactor, sealed and placed in a 100℃ oil bath for stirring and reaction for 8 hours, and then centrifuged. The centrifugal speed was set to 10000 rpm for 8 minutes to obtain three phases: mixed product phase, glycerol phase and solid catalyst phase. The obtained mixed product phase was analyzed by Agilent-7890B gas chromatograph (Agilent Technologies, USA) flame ionization detector (FID) and HP-5 capillary column (30m×0.32mm×0.50μm), and the caprylic acid (CA) conversion rate and the selectivity of medium-chain monoglyceride (MCM), medium-chain diglyceride (MCD) and medium-chain triglyceride (MCT) were calculated according to the following formulas. After analysis and calculation, it was concluded that the conversion rate of caprylic acid was 46.65%, while the selectivity of medium-chain monoglycerides, medium-chain diglycerides and medium-chain triglycerides reached 82.20%, 17.23% and 0.57%, respectively.

[0064] It can be seen from the above results that with the increase of calcination temperature, the catalytic activity of the nano-sheet pure silicon S-1 zeolite loaded with rhenium solid catalyst first increases and then decreases. When the calcination temperature is 350°C, the octanoic acid conversion rate reaches a maximum of 72.92%. Subsequently, the loading amount of Re was investigated. With the increase of the loading amount of Re, the catalytic activity of the nano-sheet pure silicon S-1 zeolite loaded with rhenium solid catalyst continued to increase, but after the loading amount reached 5%, the content of Re continued to increase, and the catalytic activity increased slowly. Therefore, the sheet pure silicon zeolite with 5% Re loading was selected for analysis, and its octanoic acid conversion rate can reach 68.16%, which is 1.7 times that of the nano-sheet pure silicon S-1 zeolite in Comparative Example 1, which shows that the introduction of metal Re can significantly improve the performance of the catalyst in catalyzing the esterification reaction. In addition, according to Comparative Example 2, it can be found that the catalytic activity of metal Re loaded on ZSM-5-p is lower than that loaded on S-1-p, which shows that Re can better reflect its metal activity on nano-sheet pure silicon zeolite. Under the same loading amount, the conversion rate of the nanosheet pure silicon S-1 zeolite loaded with rhenium solid catalyst synthesized at different calcination temperatures during loading is different, indicating that the best metal active sites are formed at 350°C, and at this temperature, the precursor of metal Re is not completely lost due to high-temperature sublimation.

[0065] The above test shows that the nano-sheet pure silica zeolite (5Re / S-1-p) solid catalyst with a 5% Re loading prepared by the present invention significantly improves the conversion rate of caprylic acid in the reaction of esterifying caprylic acid with glycerol to prepare medium-chain glycerides, and the products of the esterification of caprylic acid with glycerol catalyzed by this series of catalysts to prepare medium-chain glycerides are medium-chain glycerol monoesters, medium-chain glycerol diesters and medium-chain glycerol triesters, and the sum of the selectivities of each product is higher than 99.9%, which indicates that 99.9% of the reaction products are target products, and the product and the raw material (glycerol) are stratified, so the subsequent separation process of the target product is simple, making it more conducive to industrial promotion and application.

[0066] 5. Stability test of the reaction of esterification of caprylic acid and glycerol to prepare medium-chain glycerides catalyzed by nano-sheet pure silicon S-1 zeolite supported rhenium solid catalyst: Taking the reaction of esterification of caprylic acid and glycerol to prepare medium-chain glycerides catalyzed by nano-sheet pure silica zeolite (5Re / S-1-p) solid catalyst with 5wt%Re loading as an example, the stability of the nano-sheet pure silica zeolite solid catalyst loaded with metal Re in the catalytic esterification of caprylic acid and glycerol to prepare medium-chain glycerides was tested. During the test, the nano-sheet pure silica zeolite solid catalyst with 5wt%Re loading was repeated five times and applied to the catalytic esterification of caprylic acid and glycerol to prepare medium-chain glycerides. The specific operation method of each reaction is as follows: According to the molar ratio of caprylic acid to glycerol of 1:1, 6.26g caprylic acid and 4.00g glycerol were weighed respectively, and then 0.1g 5Re / S-1-p (350℃) catalyst was weighed. They were added to a 25ml hydrothermal reactor, sealed and placed in a 100℃ oil bath for stirring and reaction for 8h, and then centrifuged. The centrifugal speed was set to 10000rpm for 8min to obtain three phases: mixed product phase, glycerol phase and solid catalyst phase. The obtained mixed product phase was analyzed by Agilent-7890B gas chromatograph (Agilent Technologies, USA) flame ionization detector (FID) and HP-5 capillary column (30m×0.32mm×0.50μm), and the caprylic acid (CA) conversion rate and the selectivity of medium-chain monoglyceride (MCM), medium-chain diglyceride (MCD) and medium-chain triglyceride (MCT) were calculated according to the formula.

[0067] After analysis and calculation, it was concluded that the conversion rate of caprylic acid in the first reaction was 68.16%, while the selectivity of medium-chain monoglycerides, medium-chain diglycerides and medium-chain triglycerides reached 80.71%, 18.56% and 0.73%, respectively; the conversion rate of caprylic acid in the second reaction was 65.34%, and the selectivity of medium-chain monoglycerides, medium-chain diglycerides and medium-chain triglycerides were 81.28%, 17.81% and 0.99%, respectively; the conversion rate of caprylic acid in the third reaction was 62.27%, and the selectivity of medium-chain monoglycerides, medium-chain diglycerides and medium-chain triglycerides were 81.28%, 17.81% and 0.99%, respectively. The selectivities of monoglyceride, medium-chain diglyceride and medium-chain triglyceride were 82.61%, 16.79% and 0.60%, respectively; the conversion rate of caprylic acid obtained in the fourth reaction was 60.01%, and the selectivities of medium-chain monoglyceride, medium-chain diglyceride and medium-chain triglyceride were 83.02%, 16.34% and 0.64%, respectively; the conversion rate of caprylic acid obtained in the fifth reaction was 58.12%, and the selectivities of medium-chain monoglyceride, medium-chain diglyceride and medium-chain triglyceride were 83.42%, 16.10% and 0.48%, respectively.

[0068] From the above data, it can be seen that in the reaction of catalyzing the esterification of caprylic acid and glycerol to prepare medium-chain glycerides, the caprylic acid conversion rate of the nano-sheet pure silica zeolite (5Re / S-1-p) solid catalyst with a 5wt% Re loading only decreased by 10.04% after simple washing with n-hexane and acetonitrile and repeated the reaction five times, which is completely acceptable in macromolecular catalytic reactions, indicating that it has good catalytic stability and a wide range of application.

[0069] The embodiments described above only express several preferred embodiments of the present invention, and the descriptions thereof are relatively specific and detailed, but are not intended to limit the present invention. It should be noted that for those skilled in the art, the present invention may also have various changes and modifications, and any modifications, equivalent substitutions, improvements, etc. made within the concept and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a rhenium-loaded nano-sheet pure silicon S-1 zeolite catalyst, characterized in that: The preparation method comprises the following steps: Step 1: using tetraethyl orthosilicate as a silicon source, tetrapropylammonium hydroxide as a template, ammonia water and glucose as growth regulators, adopting a hydrothermal synthesis method to obtain a nano-sheet pure silicon S-1 zeolite carrier through drying and calcination; Step 2: prepare a rhenium precursor solution with ammonium perrhenate as a rhenium source, and impregnate it with the nano-sheet pure silicon S-1 zeolite carrier prepared in step 1 in equal volumes, and obtain a rhenium-loaded nano-sheet pure silicon S-1 zeolite catalyst after aging, drying and calcination; wherein the loading amount of rhenium element in the nano-sheet pure silicon S-1 zeolite carrier is 1% to 20%.

2. The method for preparing a rhenium-loaded nano-sheet pure silicon S-1 zeolite catalyst according to claim 1, characterized in that: In step 2, the loading amount of rhenium element in the nano-sheet pure silicon S-1 zeolite carrier is 2% to 10%; Preferably, in step 2, the loading amount of rhenium element in the nano-sheet pure silicon S-1 zeolite carrier is 5% to 7%; Preferably, in step 2, the loading amount of rhenium element in the nano-sheet pure silicon S-1 zeolite carrier is 5%.

3. The method for preparing a rhenium-loaded nano-sheet pure silicon S-1 zeolite catalyst according to claim 1, characterized in that: The calcination temperature in step 2 is 300°C to 500°C, and the calcination time is 4h to 6h; Preferably, the calcination temperature in step 2 is 350° C. to 450° C., and the calcination time is 4.5 h to 5.5 h; Preferably, the calcination temperature in step 2 is 350° C. and the calcination time is 5 h.

4. The method for preparing a rhenium-loaded nano-sheet pure silicon S-1 zeolite catalyst according to claim 1, characterized in that: In step 2, the drying temperature is 100° C. to 140° C., and the drying time is 6 h to 24 h; Preferably, in step 2, the drying temperature is 120° C. and the drying time is 12 h.

5. The method for preparing a rhenium-loaded nano-sheet pure silicon S-1 zeolite catalyst according to claim 1, characterized in that: In step 2, the aging is carried out in air for 12 hours to 48 hours.

6. The method for preparing a rhenium-loaded nano-sheet pure silicon S-1 zeolite catalyst according to claim 1, characterized in that: In step 1, the raw materials for preparing the nano-sheet pure silicon S-1 zeolite carrier are, according to the effective ingredients, the molar ratio of SiO2, TPAOH, NH3, Glu, and H2O is 1: (0.20-0.28): (0.5-0.7): (0.20-0.28): 10.0; Preferably, in step 1, the raw materials for preparing the nano-sheet pure silicon S-1 zeolite carrier are prepared in a molar ratio of SiO2, TPAOH, NH3, Glu and H2O of 1:0.24:0.62:0.24:10.0 based on the effective ingredients.

7. The method for preparing a rhenium-loaded nano-sheet pure silicon S-1 zeolite catalyst according to claim 1 or 6, characterized in that: In step 1, the hydrothermal crystallization temperature of the hydrothermal synthesis method is 95°C to 115°C, and the hydrothermal crystallization time is 72h to 120h; the drying temperature is 100°C to 140°C, and the drying time is 12h to 48h; the calcination temperature is 500°C to 600°C, and the calcination time is 4h to 6h; Preferably, in step one, the hydrothermal crystallization temperature of the hydrothermal synthesis method is 105°C, and the hydrothermal crystallization time is 96 hours; the drying temperature is 120°C, and the drying time is 24 hours; the calcination temperature is 550°C, and the calcination time is 5 hours.

8. The method for preparing a rhenium-loaded nano-sheet pure silicon S-1 zeolite catalyst according to claim 1, characterized in that: The following steps are involved: Step 1: Using tetraethyl orthosilicate as a silicon source, tetrapropylammonium hydroxide as a template, and ammonia and glucose as growth regulators, tetraethyl orthosilicate is added dropwise to an aqueous solution of tetrapropylammonium hydroxide, and after the addition is completed, ammonia and glucose are added thereto, the resulting mixed solution is stirred and aged at room temperature, and then hydrothermally crystallized, and the crystallized product is then washed, dried, ground, and calcined to obtain a nano-sheet pure silicon S-1 zeolite carrier; Step 2: Prepare a rhenium precursor solution with ammonium perrhenate as the rhenium source, and use the equal volume impregnation method to drop the rhenium precursor solution on the nanosheet pure silicon S-1 zeolite carrier described in step 1. After impregnation and aging treatment, it is dried, ground and calcined to obtain a rhenium-loaded nanosheet pure silicon S-1 zeolite catalyst.

9. The rhenium-loaded nanosheet pure silicon S-1 zeolite catalyst obtained by the preparation method according to any one of claims 1 to 8; Preferably, the rhenium-loaded nano-sheet pure silicon S-1 zeolite catalyst is a sheet-like MFI topological framework structure; Preferably, the thickness of the rhenium-loaded nanosheet pure silicon S-1 zeolite catalyst is 180 nm to 220 nm.

10. Use of the rhenium-loaded nano-sheet pure silicon S-1 zeolite catalyst as claimed in claim 9 in catalyzing the esterification reaction of caprylic acid and glycerol to synthesize medium-chain glycerides; Preferably, the method for catalyzing the esterification reaction of caprylic acid and glycerol to synthesize medium-chain glycerides is: using caprylic acid and glycerol as raw materials, adding a rhenium-loaded nano-sheet pure silicon S-1 zeolite catalyst, placing in a high-pressure closed container, stirring and reacting at 90° C. to 110° C. for 7 h to 9 h, centrifuging and layering after the reaction to obtain medium-chain glycerides; Preferably, the medium-chain glycerides include, by weight percentage, 73% to 87% of medium-chain monoglycerides, 10% to 25% of medium-chain diglycerides and 0.3% to 3.0% of medium-chain triglycerides.

Citation Information

Cited By

  • Nanoscale high-dispersity rhenium-based catalyst for preparing perfluorobutyl ethylene as well as preparation method and application of nanoscale high-dispersity rhenium-based catalyst

    CN121402078A